Chapter Relationship between shoreline evolution and sediment wear - López, Isabel (Proceedings e report, 2020)
The main objective to this work is to establish a relationship between shoreline evolution and sediment wear. The shoreline evolution trend is similar to of the results obtained by the accelerated particle wear test (APW). However, the relationship between the number of APW test cycles and the years of shoreline evolution is not clear. In Guardamar beach the ratio (years/cycles) is 9.7, in Marineta Casiana beach (it is 5.6, and in Arenal beach it is 3. Differences may be due to the different mineralogical composition and morphology of the sand particles.